Development of a Sustainability Model for Muslim SMEs in West Java: An Analysis of the Integration between the Triple Bottom Line and Islamic Economic Principles - Sudana, Sudana; Awaludin, Latief; Dermawan, Muhammad Jagat; Samudra, Muhammad Gilang; Andika, Galih Pribadi (Al-Muamalat: Jurnal Ekonomi Syariah, 2025)
This study aims to develop a sustainability model for Muslim Small and Medium Enterprises (SMEs) in West Java by integrating the Triple Bottom Line (TBL) concept with Islamic Economic principles. The TBL approach, which includes financial, social, and environmental aspects, is analyzed to understand its implementation. This study uses a qualitative method with a phenomenological approach. Data were collected through interviews and analyzed using NVivo. The results of the study show that Muslim SMEs in West Java prioritize financial and social aspects, while attention to the environment is still limited. From an Islamic Economic perspective, sustainability is not only seen from the financial and social aspects, but also responsibility towards the environment as a mandate. Other findings show that riba, maysir, and gharar-based financial practices exacerbate financial risks and social relationships. Therefore, the proposed sustainability model integrates all three aspects of TBL with Islamic economic principles. The main contribution of this study is the development of a sustainability model based on Islamic values that offers concrete guidance for Muslim SMEs to integrate TBL principles with sharia in a practical manner. This model provides a framework to reduce dependence on riba-based financing, increase community empowerment, and environmental management according to Islamic principles. Thus, these findings can be implemented by SMEs, policy makers, and supporting institutions to promote holistic and Islamic sustainability.